Urinary tract infection in gynaecology and obstetrics. Issue 9 (September 2020) - Krishnaswamy, Priyanka H.; Basu, Maya
Abstract: This review article explores the occurrence of urinary tract infection in women – in pregnancy, in gynaecology, after menopause as well as those that are acquired in hospitals. It discusses the pathophysiology of these infections and the evidence that is currently present for different management modalities. It also discusses in-depth, the various causes and treatment modalities for recurrent urinary tract infections including the burden that it can bear on women and society.